IMPROVE THE ABILITY OF WRITING PARAGRAPH RUMPANG THROUGH VISUAL AUDIO MEDIA IN CLASS IV STUDENTS OF SDN 1 SUWAWA SELATAN BONEBOLANGO DISTRICT (British Journal of Global Ecology and Sustainable Development, 2022)
The problem in this study is whether audio-visual media can improve the ability to write gap paragraphs in class IV students at SDN 1 South Suwawa, Bonebolango Regency? This study aims to improve the ability to write gap paragraphs through audio-visual media in class IV students at SDN 1 South Suwawa, Bonebolango Regency. This type of research is Classroom Action Research. Data collection techniques in this study were observation, testing and documentation. In the initial observations, out of 18 students, there were 6 students or 33% who were declared capable while 12 students or 67% who were declared unable to write gap paragraphs through audio-visual. In cycle I the first meeting through audio-visual media increased to 8 students or 44% who were declared capable while 10 students or 56% were declared unable. In cycle I, the second meeting increased to 11 students or 61% who were declared capable, while 7 students or 39% were declared unable. In cycle II the first meeting increased again to 15 students or 83% who were declared capable while 3 students or 17% who were declared unable from 18 students